Beta diversity of woody plants in the Japanese archipelago: the roles of geohistorical and ecological processes. (5th March 2014) - Kubota, Yasuhiro; Hirao, Toshihide; Fujii, Shin‐jiro; Shiono, Takayuki; Kusumoto, Buntarou; Veech, Joseph
Abstract Aim We addressed the roles of geohistorical and ecological factors on beta diversity patterns of woody plants in the Japanese archipelago. We scrutinized the contribution of recent diversification in shaping the woody plant diversity of insular areas in East Asia. Location The Japanese archipelago. Methods The distribution data of 1030 woody plant species were compiled for 65 localities in the archipelago. First, the relationships between geohistorical (straits, distance and area) and ecological (topographical heterogeneity, minimum temperature and annual precipitation) variables and taxonomic and phylogenetic beta diversity were tested using regression models. Second, geographical patterns of phylogenetic beta diversity were compared with those of taxonomic beta diversity using ordination and randomization tests. These analyses were applied to the woody plants overall and their functional groups defined by life‐form (coniferous, deciduous broad‐leaved and evergreen broad‐leaved groups). Results Distance and minimum temperature showed significant positive relationships with both measures of beta diversity across the woody plants overall and the functional groups. The contributions of geographical barriers, topographical heterogeneity and annual precipitation varied among groups. Ordinations by phylogenetic beta diversity produced patterns that were consistent with those generated by taxonomic beta diversity, showing three clusters of localities in relation to geographical barriers, except in the coniferous group. The regression slopes of phylogenetic beta diversity versus distance were significantly smaller than those of taxonomic beta diversity versus distance across all groups. Main conclusions In the Japanese archipelago, the combination of geographical isolation and environmental filtering in response to geohistorical perturbations and environmental gradients has configured the beta diversity patterns of woody plants. The recent diversification of phylogenetically close relatives probably caused the spatial variations that exist in woody plant diversity. The archipelago functions as a refugium for relict taxa and as a hotspot for neoendemics, contributing to the broad‐scale diversity bias favouring East Asia.